2001
DOI: 10.1016/s0893-133x(01)00233-0
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-like Activity of Tamoxifen and Raloxifene on NMDA Receptor Binding and Expression of its Subunits in Rat Brain

Abstract: Hormonal specificity of modulation of N-methyl-D-aspartate (NMDA) receptors was investigated by comparing the effects of estradiol with tamoxifen or raloxifene, which display different responses in breast, bone, and uterus. Two weeks ovariectomy in rats decreasedIt has been shown that the female sex steroid estradiol exerts profound effects on neuronal differentiation during development (Toran-Allerand et al. 1983) and recently, accumulating evidence support also a modulatory role of estrogens in the normal ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 63 publications
5
48
1
1
Order By: Relevance
“…Along these lines, estrogen has been demonstrated to increase NMDA receptor binding [234,[299][300][301], increase NMDAR1 and NMDAR2b gene expression in CA1 region of the hippocampus of rats [302,303], and enhance NMDAdependent calcium signals in CA1 spines and dendrites [304]. Furthermore, NMDA receptor antagonists have been shown to block the estrogen-induced increase in spine density in the CA1 of the hippocampus [239,295,296].…”
Section: Mechanisms Of Estrogen Regulation Of Synaptic Plasticitymentioning
confidence: 98%
“…Along these lines, estrogen has been demonstrated to increase NMDA receptor binding [234,[299][300][301], increase NMDAR1 and NMDAR2b gene expression in CA1 region of the hippocampus of rats [302,303], and enhance NMDAdependent calcium signals in CA1 spines and dendrites [304]. Furthermore, NMDA receptor antagonists have been shown to block the estrogen-induced increase in spine density in the CA1 of the hippocampus [239,295,296].…”
Section: Mechanisms Of Estrogen Regulation Of Synaptic Plasticitymentioning
confidence: 98%
“…Estradiol increases NR2B subunit mRNA, the number of NR2B binding sites, and the synaptic localization of NR2B-containing receptors (Cyr et al, 2001;Adams et al, 2004). It is currently unknown whether the estradiol-induced increase in NMDAR transmission is attributable to the increase in synaptic localization of NR2B-containing receptors.…”
Section: Introductionmentioning
confidence: 99%
“…It is currently unknown whether the estradiol-induced increase in NMDAR transmission is attributable to the increase in synaptic localization of NR2B-containing receptors. Furthermore, whether the increase in synaptic NR2B-containing receptors results from expression of new receptors or from lateral movement of existing receptors into the synapse is an open question (Cyr et al, 2001;Adams et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we also see sexual dimorphism in NMDAR expression which may be due in part to estrogen-mediated regulation of its subunits. Previous studies have demonstrated reduced NMDAR binding density and GluN1 and GluN2A expression in the hippocampus following ovariectomy, and reversal of this with estradiol treatment [39]. The ability of estrogen to enhance long-term potentiation at hippocampal synapses is also dependent on NMDARs [40].…”
Section: Discussionmentioning
confidence: 95%